Students' Critical Thinking Ability Through the Application of the Creative Problem Solving (CPS) Model assisted by Autograph - Zulfikar Zulfikar; Zainal Azis; Marah Doli Nasution (JMEA : Journal of Mathematics Education and Application, 2022)
This study aims to examine differences in critical thinking skills between groups of students who apply Autograph-aided Creative Problem Solving learning models and students who apply Creative Problem-Solving learning models without the help of autographs and see students' positive attitudes in learning Creative Problem-Solving models. This research is experimental research at YPK Medan Private Middle School. The sample selection used as the experimental group, and the control group was carried out randomly (random cluster sampling). The instrument used was a set of tests of critical thinking skills in mathematics. The results showed that the ability to think critically in students who applied the CPS model using Autograph was better, with a percentage of mastery learning by 85.27%. In comparison, the group of students who applied the CPS model gained a percentage of mastery learning by 78.16%. There was a positive attitude of students applying the autograph-aided CPS model when learning takes place.